2018
DOI: 10.1159/000491652
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circular RNAs Altered in Mouse Jejuna After Radiation

Abstract: Background/Aims: Circular RNAs (circRNAs) make up a large class of non-coding RNAs and play important roles in a variety of diseases, including nervous system diseases and cancers. The intestinal epithelium is sensitive to ionizing radiation, radiotherapy of abdominal or pelvic tumors or nuclear accident exposure can lead to high radiation toxicity, which can result in radiation-induced intestinal injury. The goal of this present study was to analyze the potential roles of circRNAs in radiation-induced intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…Although our laboratory has found that mesenchymal stem cell and 6‐shogaol can improve animal survival and intestinal function following irradiation injury, we still need to understand more about the effects of radiation in order to solve the problem of radiation‐induced intestinal damage from the effect itself. Therefore, our previous work has analysed the regulatory network of circRNAs in radiation‐induced intestinal injury, as well as some important responses of mRNAs . In this article, we focus on the role of lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Although our laboratory has found that mesenchymal stem cell and 6‐shogaol can improve animal survival and intestinal function following irradiation injury, we still need to understand more about the effects of radiation in order to solve the problem of radiation‐induced intestinal damage from the effect itself. Therefore, our previous work has analysed the regulatory network of circRNAs in radiation‐induced intestinal injury, as well as some important responses of mRNAs . In this article, we focus on the role of lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The BioAnalyzer 2100 system was used for ensuring quality control and library quantification. Then, 10-pM libraries were denatured into single-stranded DNA molecules, captured on Illumina flow cells, amplified in situ , and clustered, and finally, 150 cycles of sequencing were performed on the Illumina HiSeq sequencer according to the manufacturer’s instructions ( Lu et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…According to the manufacturer's instructions (Lu et al, 2018), Trizol (Invitrogen, Carlsbad, CA, United States) was used to extract RNA from the lacrimal glands of both AQP5 +/+ and AQP5 −/− mice, and the optical density (OD 260/280 ) value was determined by using a NanoDrop ND-2000 instrument (Thermo Fisher Scientific, Waltham, MA, United States) to measure the RNA concentration. RNA integrity was determined by agarose gel electrophoresis.…”
Section: Extraction and Separation Of Rna Samplesmentioning
confidence: 99%
“…RNA was isolated from the control group and the irradiation group using TRIzol reagent (Invitrogen, Carlsbad, California) according to the manufacturer’s instructions. 9 Each of the RNA sample concentration was measured using a NanoDrop ND-2000 instrument (Thermo, Waltham, Massachusetts). Besides, denaturing agarose gel electrophoresis was used to assess the integrity of RNA.…”
Section: Methodsmentioning
confidence: 99%
“…Ten pM libraries were denatured as single-stranded DNA molecules, captured on Illumina flow cells, amplified in situ as clusters and finally sequenced for 150 cycles on Illumina HiSeq Sequencer according to the manufacturer’s instructions. 9…”
Section: Methodsmentioning
confidence: 99%